The Aftermath of Divorce: Postdivorce Adjustment Strategies of South Asian, Black, and White Women in the United States. Issue 6 (17th August 2016) - Lawson, Erma J.; Satti, Filza
ABSTRACT: This article explores South Asian women's narratives of postdivorce coping strategies and compares such reactions to those of divorced Black and White U.S. women. Using a resiliency, gendered framework embedded within a sociocultural perspective, the findings report that women coped with divorce by (a) "keeping busy, " (b) reliance on family support, (c) and religious and spirituality involvement. However, cultural traditions, values, and norms influenced postdivorce definitions of postdivorced coping strategies. Parenthood occupied a large percentage of the Pakistani respondents' time, whereas Black and White Americans restructured their lives through a variety of activities. All respondents relied on family and religious support to reduce postdivorce distress, but the enactment of such strategies was embedded within social cultural contexts such as immigration, race, class, gender, culture, religion, and intergenerational status. This article emphasizes the importance of including diverse voices of women in postdivorce adjustment research, and challenges the popular images of divorced women as passive, inactive, and despairing victims waiting to be rescued by Prince Charming. The findings also reveal that women forged new models of human connectedness and turned despair into determination to succeed, demonstrating their resiliency. Finally, it calls for studies on postdivorce adjustment, immigration, and resiliency from a gender-sensitive comparative perspective. Failure to do so results in generalizations and prohibits an understanding of sociocultural factors that decrease postdivorce distress.